A Retrospective Study on a Hospital-Based Cleft Care Center in Shanghai. Issue 2 (March 2015) - Wang, Daohe; Xu, Haisong; Qi, Fazhi; Chen, Yang; Gu, Jianying
<x xml:space="preserve">Abstract</x> Objective The objective of this investigation was to describe the characteristics of the current cleft treatment situation in a hospital-based cleft center in Shanghai and provide references to clinical diagnosis, treatment, and nursing. Methods A total of 1584 patients from the Center for Cleft Lip and Palate, Department of Oral and Cranio-Maxillofacial Science, Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine during June 2006 to February 2008 were analyzed retrospectively. Data regarding sex, native place, type of cleft, cleft side, accompanied malformations, family history, and age at surgery were analyzed in detail. Length of stay after surgery, the primary operation fee, and some other hospitalized information were also investigated. Results From 1584 patients(1590 operations; 6 patients had 6 operations), there were 939 male and 645 female patients (M:F = 1.46:1). The number of Shanghai local patients is 249 (15.72%), whereas the other 1335 patients were from out of Shanghai. Approximately 15% of the patients had certain family history. The age at operating varied from 2 months to 36 years; the mean value was 6.95 years. The postoperation hospital stay varied from 1 day to 15 days; the mean value was 5.54 days. The primary operation fee was 235 to 673 USD depending on the different surgical procedures. The number of cleft types or other malformation, which had not been treated in the statistics varied from zero to 3; the mean value was 0.4375. The cleft morphology was classified as follows: cleft lip, 591 cases (37.31%); cleft palate, 651 cases (41.10%); alveolar cleft, 144 cases (9.10%); facial traverse cleft, 27 cases (1.70%); velopharyngeal insufficiency, 105 cases (6.63%); velocardiofacial syndrome, 57 cases (3.60%); and Pierre Robin sequence, 15 cases (0.95%). In all the classifications, left was more than right (L:R = 2.10:1). Conclusion As a busy hospital-based cleft care center, most of the patients are from out of Shanghai. The current multidisciplinary protocol for cleft care in such specialist cleft center is cost-effective. There may be a tendency that the patients with cleft palate are more than the patients with cleft lips in recent years, which may due to the popularization of prenatal examination in China.